PELAKSANAAN KESEHATAN DAN KESELAMATAN KERJA DI DEPARTEMEN HOUSEKEEPING HOTEL THE ZURI PEKANBARU - Eko Putra Pratama; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru is the capital city of Riau Province which has excellent potential in tourism and business. Hotel The Zuri is a millennial hotel that suitable for leisure and business. Where's the hotel with the highest swimming pool in Pekanbaru.  This study aims to determine the implementation of health and occupational safety (K3) at the Housekeeping Department, Hotel The Zuri Pekanbaru. This study used a qualitative descriptive method to comply with the problem analysis based on data collection techniques in the form of observation, interviews, and documentation. The implementations of occupational health and safety include occupational health problems, the scope of occupational health, health problems that may occur due to work, prevention of occupational health and safety problems, principles of occupational health and safety, and basic principles of assisting accidents. Based on the results of the study, conclusions can be drawn that the implementation of occupational health and safety in the Housekeeping Department of The Zuri Hotel Pekanbaru has been carried out well but has not fully complied with the standard operating procedures of K3.                                                                                         Keywords: Hotel, Housekeeping, Occupational Health and Safety